60: Women's Experiences of the Prenatal Consultation for Preterm Labor: Neonatologists as Highlights, and Opportunities for Improvement. Issue 6 (1st June 2014) - Gaucher, N; Nadeau, S; Barbier, A; Payot, A
Abstract: BACKGROUND: Recommendations about prenatal counseling for pre-term labor, based on expert opinions, emphasize informing parents. Mothers' perspectives are lacking. OBJECTIVES: To evaluate mother's experiences of prenatal consultations for preterm labor. DESIGN/METHODS: This was a prospective survey of hospitalized women at risk of preterm delivery 26 to 32 weeks GA, who had met the neonatologist for prenatal consultation within the last 72 h.The tool was developed using data from a qualitative exploratory study; construct and content validity were accounted for through several validation phases. A single-center pilot study was conducted in 2008, leading to a multicenter trial in three tertiary care university hospitals (April 2012 to September 2013). Variables were analyzed using Chi2 and Student T-tests. RESULTS: A total of 229 of 334 surveys were returned (67.2%). Sixty-five percent of consultations were performed by one healthcare provider, with neonatologists providing most explanations (77.9%). Participants' overall experiences were positive (89.9%). Consultations lasted 10 min to 20 min (68.1%); length of meeting was associated with women feeling informed about prematurity, prepared for their role as mother, and reassured (P<0.001). Complications of prematurity were explained adequately for 53.9% of women and in too much detail for 39.3%. Sixteen percent of women did not receive data on prematurity's complications; of those who did, most obtained it in general terms (72.0%). After the meeting, women felt very well informed about prematurity (mean 4.4 on a 5-point Likert scale), but they felt less well prepared as the mother of a premature baby (mean 3.65; P<0.001). More highlights and potential improvements are presented in the table. CONCLUSIONS: Prenatal consultations with a neonatologist are strongly appreciated. Information about prematurity predominates the physicians' discourses. This study informs clinicians about potential improvements, especially in light of mothers' priorities..